Anpao : an American Indian odyssey - Highwater, Jamake; Scholder, Fritz, 1937-2005; Eisenberg, Pablo; Younghee Kim-Wait (Class of 1982)/Pablo Eisenberg Collection of Native American Literature (1977)
Traditional tales from North American Indian tribes woven into one story that relates the adventures of one boy as he grows to manhood.
In the days of the plentiful -- Dawn of the world -- Lessons of heaven and earth -- Invasion from the sea -- Storyteller's farewell -- Notes on sources -- Bibliography.
Amherst College Archives and Special Collections copy is in dust jacket. [Note: Author Jamake Highwater (also known as Jay Marks) self-identified as Indian. This has been disputed. Cf. Finding Aid for the Jamake Highwater Papers at the New York Public Library.]
Bibliography: p. 253-254.
Newbery Honor Book, 1978.
Keywords: Indians of North America -- Folklore; Luiseño Indian artists; Juvenile literature